First experimental study of photon polarization in radiative B0s decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review letters, 2017)
The polarization of photons produced in radiative B0s decays is studied for the first time. The data are recorded by the LHCb experiment in pp collisions corresponding to an integrated luminosity of 3 fb−1 at center-of-mass energies of 7 and 8 TeV. A time-dependent analysis of the B0s→ϕγ decay rate is conducted to determine the parameter AΔ, which is related to the ratio of right- over left-handed photon polarization amplitudes in b→sγ transitions. A value of AΔ=−0.98+0.46−0.52+0.23−0.20 is measured. This result is consistent with the standard model prediction within 2 standard deviations.
Im Titel sind "0" und "s" untereinander geschrieben: "0" hoch-, "s" tiefgestellt
R. Aaij, P. d’Argent, S. Bachmann, S. Braun, M. Britsch, A. Comerma-Montells, M. De Cian, S. Esen, D.Gerick, E. Gersabeck, X.Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, M. Kolpin, K. Kreplin, B. Leverington, J. Marks, M. Meissner, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, A. Piucci, P. Seyfert, M. Schiller, M. Stahl, J. v. Tilburg, U. Uwer, M. Vesterinen, R. Waldi, A. Zhelezov [und weitere]
published 9 January 2017; corrected 28 February 2017
Gesehen am 30.10.2018